A registry-based study evaluating overall survival and treatment duration in Swedish patients with metastatic castration-resistant prostate cancer treated with enzalutamide. (3rd September 2019) - Alghazali, Mohammed; Löfgren, Annica; Jørgensen, Leif; Svensson, Maja; Fagerlund, Karin; Bjartell, Anders
Abstract: Objective: This retrospective, single-centre, non-interventional, registry-based study evaluated patients with metastatic castration-resistant prostate cancer (mCRPC) treated with enzalutamide in daily clinical practice at Skåne University Hospital, Malmö, Sweden. Materials and methods: Registry data were reviewed for patients treated with enzalutamide pre- or post-chemotherapy initiated between December 2013 and June 2017. The primary endpoint was overall survival (OS) in post-chemotherapy patients. Secondary endpoints were enzalutamide treatment duration in the pre- and post-chemotherapy setting. This study was approved by the Lund regional Ethics Review Board (Dnr:2017/716) and is registered with ClinicalTrials.gov (NCT03328364). Results: A total of 102 pre-chemotherapy and 98 post-chemotherapy patients were included. Median age was higher in the pre- than in the post-chemotherapy group (77 vs 72 years, respectively). Median OS in post-chemotherapy patients from initiation of enzalutamide until death from any cause was 14.3 months [95% confidence interval (CI) = 11.00–18.20]. Median treatment duration was 13.8 months (95% CI = 11.4–20.2) and 7.6 months (95% CI = 6.3–10.2) for pre- and post-chemotherapy patients, respectively. Conclusion: Enzalutamide can be used to effectively treat mCRPC patients in daily clinical settings, despite the patients being older and less healthy than those enrolled in the previous randomised, clinical registration studies.